Glargine and degludec: solution behaviour of higher dose synthetic insulins - Adams, Gary G.; Alzahrani, Qushmua; Jiwani, Shahwar I.; Meal, Andrew; Morgan, Paul S.; Coffey, Frank; Kok, Samil; Rowe, Arthur J.; Harding, Stephen E.; Chayen, Naomi; Gillis, Richard B. (Nature Publishing Group, 2017)
Single, double and triple doses of the synthetic insulins glargine and degludec currently used in patient therapy are characterised using macromolecular hydrodynamic techniques (dynamic light scattering and analytical ultracentrifugation) in an attempt to provide the basis for improved personalised insulin profiling in patients with diabetes. Using dynamic light scattering and sedimentation velocity in the analytical ultracentrifuge glargine was shown to be primarily dimeric under solvent conditions used in current formulations whereas degludec behaved as a dihexamer with evidence of further association of the hexamers (“multi-hexamerisation”). Further analysis by sedimentation equilibrium showed that degludec exhibited reversible interaction between mono- and-di-hexamer forms. Unlike glargine, degludec showed strong thermodynamic non-ideality, but this was suppressed by the addition of salt. With such large injectable doses of synthetic insulins remaining in the physiological system for extended periods of time, in some case 24–40 hours, double and triple dose insulins may impact adversely on personalised insulin profiling in patients with diabetes.